2019
DOI: 10.21873/anticanres.13478
|View full text |Cite
|
Sign up to set email alerts
|

Potential Molecular Mechanisms of the Anti-cancer Activity of Vitamin D

Abstract: Vitamin D, or more precisely its active metabolite calcitriol (1, 2 D 3 ), plays a fundamental role in bone metabolism and differentiation as well as in intestinal absorption of calcium and regulation of calcium-phosphate metabolism. Recent decades have brought about the discovery of the role of calcitriol in processes regulating cell differentiation, proliferation, angiogenesis and apoptosis. This creates the potential for numerous therapeutic applications of vitamin D in diseases associated with autoaggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 122 publications
0
27
0
Order By: Relevance
“…In recent years, evidence from preclinical and clinical studies has suggested that vitamin D supplementation may decrease the risk of many cancers 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, evidence from preclinical and clinical studies has suggested that vitamin D supplementation may decrease the risk of many cancers 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that vitamin D may improve survival time in patients with undifferentiated, but not differentiated carcinoma. In-vitro experiments [2,3,4] have shown the potential for vitamin D to induce differentiation of undifferentiated cancer cells in vivo. In fact, a clinical pilot trial indicated that vitamin D may increase differentiation in the normal colorectal mucosa of patients with colorectal adenoma [22], although that trial did not include patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The 25(OH)D is further activated in the kidneys by 1-alpha-hydroxylase to 1,25-dihydroxyvitamin D, which facilitates calcium absorption and plays an important role in bone health. A more recent discovery that most tissues, as well as cancers, have 1-alpha-hydroxylase to convert serum 25(OH)D to 1,25(OH)2D, along with vitamin D receptors, which are steroid hormone nuclear receptors that regulate a variety of genes within a cell [1], has provided new insights into the function of vitamin D. In particular, vitamin D has been demonstrated to induce differentiation of cancer cells in vitro [2,3,4], which leads to the hypothesis that vitamin D supplementation may improve prognosis of patients with poorly differentiated carcinoma in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is activated in the skin through sun exposure, promotes the absorption of calcium and phosphorus in the intestine and maintains an adequate concentration of these minerals in the circulation to allow for normal bone mineralisation (1) . Recently, many studies have reported non-skeletal actions on cell proliferation and differentiation (2) , immune regulation (3) , anti-tumour activity (4) and muscle function (5) associated with vitamin D. Additionally, since it has been suggested that vitamin D deficiency or insufficiency is associated with an increased risk of non-skeletal health conditions, including cardiovascular diseases such as elevated blood pressure (6) , diabetes mellitus (7) , obesity (8) , infections (9) and autoimmune diseases (10) , the importance of vitamin D has gained increasing attention. Also, vitamin D insufficiency is known to be associated with sexual dysfunction in apparently healthy women and with erectile dysfunction in men (11) .…”
mentioning
confidence: 99%